Keratin‐18 and microRNA‐122 complement alanine aminotransferase as novel safety biomarkers for drug‐induced liver injury in two human cohorts. (14th October 2013) - Thulin, Petra; Nordahl, Gunnar; Gry, Marcus; Yimer, Getnet; Aklillu, Eleni; Makonnen, Eyasu; Aderaye, Getachew; Lindquist, Lars; Mattsson, C. Mikael; Ekblom, Björn; Antoine, Daniel J.; Park, B. Kevin; et al.
Abstract Background & Aims There is a demand for more sensitive, specific and predictive biomarkers for drug‐induced liver injury (DILI) than the gold standard used today, alanine aminotransferase (ALT). The aim of this study was to qualify novel DILI biomarkers (keratin‐18 markers M65/M30, microRNA‐122, glutamate dehydrogenase and alpha‐foetoprotein) in human DILI. Methods Levels of the novel biomarkers were measured by enzyme‐linked immunosorbent assay or real‐time quantitative reverse‐transcription PCR (qRT‐PCR) in two human DILI cohorts: a human volunteer study with acetaminophen and a human immunodeficiency virus (HIV)/tuberculosis (TB) study. Results In the acetaminophen study, serum M65 and microRNA‐122 levels were significantly increased at an earlier time point than ALT. Furthermore, the maximal elevation of M65 and microRNA‐122 exceeded the increase in ALT. In the HIV/TB study, all the analysed novel biomarkers increased after 1 week of treatment. In contrast to ALT, the novel biomarkers remained stable in a human cohort with exercise‐induced muscular injury. Conclusions M65 and microRNA‐122 are potential biomarkers of DILI superior to ALT with respect to sensitivity and specificity.